Resolvin D1 Modulates the Intracellular VEGF-Related miRNAs of Retinal Photoreceptors Challenged With High Glucose - Maisto, Rosa; Trotta, Maria Consiglia; Petrillo, Francesco; Izzo, Sara; Cuomo, Giovanna; Alfano, Roberto; Hermenean, Anca; Barcia, Jorge Miquel; Galdiero, Marilena; Platania, Chiara Bianca Maria; Bucolo, Claudio; D’Amico, Michele (Frontiers in Pharmacology, 2020)
Stimulation of retinal photoreceptors with elevated glucose concentration (30 mM) for 96 h, served as diabetic retinopathy in vitro model to study Resolvin D1 (50 nM) effects on neovascularization. VEGF and anti-angiogenic miR-20a-3p, miR-20a-5p, miR-106a-5p, and miR-20b expression was assessed either in photoreceptors exposed to HG or in exosomes released by those cells. High glucose increased VEGF levels and concurrently decreased anti-angiogenic miRNAs content in photoreceptors and exosomes. RvD1 reverted the effects of glucose damage in photoreceptors and exosomal pro-angiogenic potential, tested with the HUVEC angiogenesis assay. By activating FPR2 receptor, RvD1 modulated both the expression of anti-angiogenic miRNA, which decrease VEGF, and the pro-angiogenic potential of exosomes released by primary retinal cells. HUVEC transfection with miR-20a-3p, miR-20a-5p, miR-106a-5p, and miR-20b antagomirs, followed by exposure to exosomes from photoreceptors, confirmed the VEGF-related miRNAs mechanism and the anti-angiogenic effects of RvD1.